Writing Through Tears: Women, Grief and Hope in the Academy - Badenhorst, Cecile; McLeod, Heather; Boachie, Abena Omenaa; Haghighat, Bahar; Halfyard, Julia; Toll, Haley (Journal of the Canadian Association for Curriculum Studies, 2024)
Grief shatters the body, at once collapsing inwards while simultaneously tearing apart. Is there room for grief in the neoliberal academic body? Is there space for small everyday losses as well as large life-changing losses? What do we do when our workspaces silence our grief? As academics, we are subject to a competitive, pressurized working culture resulting in increasing stress, anxiety, exhaustion. We have also experienced a devastating global pandemic. Yet, grief and loss are not emotions we readily acknowledge in our workspaces. Inspired by Shelton and Sieben (2020), we focus on this very topic and emotion, which has affected us in different ways. We bring grief (deep sorrow from death or loss) centre-stage as a way of speaking-back, stepping away from the competition and the success narratives. We use Hendry et al.’s (2018) notion of narrative as being which shifts methodology from a mode of production to a way of being in the world. Our narratives show that loss, even while experienced individually, is felt communally. Grief matters and in writing about grief, we resist neoliberal knowledge, an act which gives us hope.